Prognostic role of hematologic parameters of metastatic renal cell carcinoma treated with sunitinib. Issue 5 (October 2022) - Bolzacchini, Elena; Giordano, Monica; Bertù, Lorenza; Bregni, Marco; Nigro, Olga; Galli, Luca; Antonuzzo, Andrea; Artale, Salvatore; Barzaghi, Sabrina; Danova, Marco; Torchio, Martina; Pinotti, Graziella; et al.
Background: Hemochrome parameters at the diagnosis of metastatic renal cell carcinoma (mRCC) and the development of macrocytosis during sunitinib therapy are considered prognostic. Objective: To evaluate the prognostic role of hematologic parameters and macrocytosis in mRCC treated with sunitinib. Methods: We analyzed clinical data of 100 patients with mRCC treated with sunitinib as first-line therapy in a retrospective multicenter study. We calculated neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) at baseline and erythrocyte mean corpuscular volume (MCV) during therapy. We considered the following cutoffs: NLR >3, PLR >150, LMR <3, and MCV >100 fl. Clinical data histology, prior nephrectomy, Fuhrman grading, metastatic sites, Memorial Sloan-Kettering Cancer Center score, and Heng score were collected. Overall survival (OS) and progression-free survival (PFS) were calculated. Univariate and multivariate analysis using Cox regression model with time-dependent (macrocytosis) covariate were applied. Results: At the univariate analysis, low LMR was associated with shorter PFS and OS ( p = 0.02 and p = 0.06, respectively). High PLR was associated with worse PFS ( p = 0.005); median OS was 23 vs 28 months ( p = 0.13). At the multivariate analysis, poor risk (Heng score), low LMR, and high PLR were associated with shorter PFS (hazard ratio 7.1, 1.5, and 2, respectively); poor PS and poor risk (Heng score) were related to worst OS. Macrocytosis was observed in 26 patients and was not prognostic of survival. Conclusions: In our cohort of patients with mRCC treated with sunitinib, low LMR (>3) and high PLR (>150) were associated with shorter PFS. Macrocytosis was not prognostic.